Biology, Ecology and Management of Crown-of-Thorns Starfish - Morgan Pratchett (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Outbreaks of crown-of-thorns starfish (Acanthaster spp.) are a major contributor to ongoing coral loss on reefs throughout the Indo-Pacific, thereby jeopardizing productivity and biodiversity of these important marine ecosystems. Controlling outbreak populations of Acanthaster spp. is considered one of the most promising strategies to halt or reverse widespread declines in live coral cover. Effective management of crown-of-thorns starfish is, however, conditional on improved understanding of their biology and ecology. While crown-of-thorns starfish are arguably the most extensively studied of any single coral reef species, there remain considerable gaps in our knowledge of their basic biology and ecology. This edited monograph presents the latest research and significant advances in understanding and managing outbreaks of crown-of-thorns starfish.